Impact of Yoga on the Mental Health of B.Ed., Trainees - Govindaraj, M.; Tamizhselvan, T. (International Journal of Psychosocial Rehabilitation, 2019)
This is a quasi-experimental study to find out the impact of Yogic practices on Mental Health of the B.Ed., Trainees. 44 B.Ed., Trainees were selected and they were given Yoga practices for three months under the supervision of and guidance of Yoga Masters. The impact was found using the Mental Health trait Inventory and it was found that there is significant impact of Yogic Practices on the Mental Health of the B.Ed., Trainees.